NEW ALBIFLORUS FORMS OF VASCULAR PLANTS ON THE RUSSIAN FAR EAST - Fedina, L. A.; Maslov, M. V.; Gorovoy, P. G. (Acta Biologica Sibirica, 2016)
New atypical forms of color of the flowers for asian species: Corydalis buschii Nakai forma albiflora Fedina et Maslov (Papaveraceae), Asyneuma japonicum (Miq.) Brique forma albiflora Fedina et Kovalev (Campanulaceae), Campanula cephalotes Nakai forma albiflora Fedina et Kovalev (Campanulaceae) are found. Cypripedium macranthon Sw. forma album (Mandl) Gorovoi (Orchidaceae) with white flowers is considered.